KARAKTERISTIK BAHASA DALAM NOVEL-NOVEL KARYA HAMKA: KAJIAN STILISTIKA - Annisa, 1Khalifah; Darwis, 2Muhammad; Nurhayati, Nurhayati (Universitas Hasanuddin, 2017)
The Language Characteristics in Novels of Hamka’s Work: A Stylistic Study (Supervised by Muhammad Darwis and Nurhayati). The research aimed at describing the language characteristics of in the novels of Hamka’s work based on: (1) the characteristic of the compound words; (2) characteristic of the transitive verbs; and (3) the characteristic of the noun phrases. This was a qualitative research using the descriptive method. The research the stylistic approach. The data resources were the sentences containing the compound words, transitive verbs, noun phrases found in Hamka’s novels. Samples were taken using the purposive sampling technique. The method used to collect data was the scrutinized method using the documentation and note-taking techniques. The research result indicates that the compound words, transitive verbs, and noun phrases in the novels: “Di Bawah Lindungan Ka’bah”, “Tenggelamnya Kapal Van der Wijck, and “Merantau ke Deli” are used efficiently by Hamka to form specific methapor figurative language. The next results concerning the compound words, transitive verbs, and noun phrases of Hamka’s creativity results are: (1) the compound words represents the combination between the concrete and abstract nouns with pattern D-M (modified-modifying); (2) the transitive verbs (affix meng-kan) are combined with the abstract nouns; (3) the noun phrases are the combination between the nouns and adjective with the pattern D-M (modified-modifying); (4) the compound word, transitive verbs, and noun phrases have the semi-idiomatic characteristic, and (5) the compound words, transitive word, and noun phrases produce the concretization effect, so that they stimulate the association of the daily life reality which can create the aesthetic impression the readers inner sense.Key words: Language characteristic, compound word, transitive verb, noun phrase